TEKNOLOGI SAMBUNG MINI UNTUK MENDAPATKAN BIBIT TANAMAN DURIAN UNGGUL BAGI MASYARAKAT PEKEBUN DURIAN DI BATU BUSUK - Shalati Febjislami; P.K. Dewi Hayati; Sutoyo Sutoyo; Panca Jarot Santoso (LPPM Universitas Andalas, 2020)
Batu Busuk village, Lambung Bukit, Pauh Sub-district, Padang City is one of the durians producing centre that is known for its good fruit quality. As a smallholding's plantation, durian is subsistence cultivation with minimum preservation. Generally, the durian plant derived from seed multiplication, hence the quality of the product is not uniform and less productive. It is, therefore, necessary to transfer the appropriate technology that can provide seedlings in a short time and fast, simple implementation with a high success rate. Mini-grafting technology becomes a solution for the rejuvenation of durian in Batu Busuk. The community activities start in 2018 and persist in 2020. Durian nursery has carried out from July 2019, and the distribution of seedlings to the community has conducted in February 2020. The methods of transfer technology were counselling, plot demonstration and training to the durian planter community. Based on results, the problem in providing seedlings for rejuvenation of durian plants in Batu Busuk can be overcome by supplying seedlings from mini-grafting implementation. The nursery of durian with mini-grafting technology was successfully carried out and gained approximately 1100 seedlings. The mini-grafting success rate performed by durian planters reached 43%, indicating that skills play a fundamental role in the success rate of grafting on durian. Evaluation of the root stock growth demonstrated that we could use medium- and large-sized seeds from any variety of durian as rootstock due to its better growth performance. Hence, the mini-grafting technology on durian nursery activity must be maintained independently and sustainably by using the scion derived from its superior local durian in order to the advancement of durian of Batu Busuk.